2007
DOI: 10.1142/s100538670700034x
|View full text |Cite
|
Sign up to set email alerts
|

Automorphism Groups of Connected Cubic Cayley Graphs of Order 4p

Abstract: For a prime p, let D4p be the dihedral group 〈a,b | a2p = b2 = 1, b-1ab = a-1〉 of order 4p, and Cay (G,S) a connected cubic Cayley graph of order 4p. In this paper, it is shown that the automorphism group Aut ( Cay (G,S)) of Cay (G,S) is the semiproduct R(G) ⋊ Aut (G,S), where R(G) is the right regular representation of G and Aut (G,S) = {α ∈ Aut (G) | Sα = S}, except either G = D4p (p ≥ 3), Sβ = {b,ab,apb} for some β ∈ Aut (D4p) and [Formula: see text], or Cay (G,S) is isomorphic to the three-dimensional hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Let p and q be two primes. In [26,27,28], all connected cubic non-normal Cayley graphs of order 2pq are determined. For more results on the normality of Cayley graphs, we refer the reader to [11,19,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let p and q be two primes. In [26,27,28], all connected cubic non-normal Cayley graphs of order 2pq are determined. For more results on the normality of Cayley graphs, we refer the reader to [11,19,23].…”
Section: Introductionmentioning
confidence: 99%
“…This family of graphs has been investigated in several recent research papers (see, for example, [3,28,29]). In this paper, it is shown that Γ n is a Cayley graph, and its full automorphism group is isomorphic to Z 3 2 S 3 for n = 2, and to Z n 2 D 2n for n > 2.…”
Section: Introductionmentioning
confidence: 99%
“…Since R = 1, we have N = T 1 × · · · × T ∼ = T , where T i ∼ = T is nonabelian simple. By [10], T is one of the following: (Cay(G, S)) is soluble, this case is also excluded, see [18,Lemma 2.2].…”
Section: Proof By Lemma 43 W Is Normal In Xmentioning
confidence: 99%
“…The following six results about vertex‐transitive graphs will be needed in the remainder of the paper. The second one is obtained by combining together results from 8, 41, 42. The third one is obtained by combining together [9, Theorem 3.2 and Corollary 3.6] and [43, Theorem 2.1].…”
Section: Preliminariesmentioning
confidence: 99%